Comparison of marginal adaptation between a monoincremental resin with sonic activation and a conventional resin. - Javier Villa; Rosemarie Meier; Patricio Ruiz; Diego Halabí (Universidad de Concepción., 2015)
Aim: To determine differences in marginal adaptation between a conventional composite resin and a monoincremental resin with sonic activation. Materials and methods: 32 composite resin discs of 2.5mm in diameter and 2mm thick were fabricated in a propylene matrix and distributed in 2 groups of 16 samples each. Groups 1 FiltekTMZ350XT resin; Group 2 SonicFillTM resin with sonic activation. The gap generated between the resin and the matrix as a result of the polymerization shrinkage was analyzed in microns using a microscope at a magnification of 40X. The percentage of the lineal polymerization shrinkage was also calculated. To calculate differences in marginal adaptation between the two resins statistical analysis was performed using the unpaired t-test. Results: The extent of the gaps measured in microns and their respective standard deviations were SonicFillTM 9.95±3.05 and FiltekTMZ350XT 10.21±5.14 (p=.86). Conclusion: The use of the monoincremental resin system with sonic activation shows a marginal adaptation similar to that of conventional resin composites, with no statistically significant differences between the studied resins.